2011
DOI: 10.1136/sti.2010.047209
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and HIV risk behaviour in Central and Eastern European migrants in London

Abstract: Background Accession of 10 Central and Eastern European (CEE) countries to the EU resulted in the largest migratory influx in peacetime British history. No information exists on the sexual behaviour of CEE migrants within the UK. The aim of this study was to assess the sexual lifestyles and health service needs of these communities. Methods A survey, delivered electronically and available in 12 languages, of migrants from the 10 CEE accession countries recruited from community venues in London following extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Although according to a study among central and eastern European (CEE) migrants to London [7], reports of prior STIs in this group were lower than in the general British population, 1.1% reported being HIV positive; this is a substantially higher prevalence than is estimated for British residents (0.09%). Of note, the majority (79%) of respondents from the CCE migrants study who reported being HIV positive were Polish by birth.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although according to a study among central and eastern European (CEE) migrants to London [7], reports of prior STIs in this group were lower than in the general British population, 1.1% reported being HIV positive; this is a substantially higher prevalence than is estimated for British residents (0.09%). Of note, the majority (79%) of respondents from the CCE migrants study who reported being HIV positive were Polish by birth.…”
Section: Introductionmentioning
confidence: 97%
“…While some recent research conducted in Europe [7,8,9], as well as in some other continents [10,11], has pointed to international migration as being one of the factors influencing risky sexual behaviors, the change in these behaviors at an individual level after migration has not been thoroughly quantified to a satisfactory level [12,13]. Gaining insight into the differences in sexually transmitted infections (STIs) risk behavior patterns between pre- and post-migration stages can provide a broader contextual understanding of how the shift from these two migration stages specifically impacts such behavior.…”
Section: Introductionmentioning
confidence: 99%
“…1 People, including migrants to the UK visiting their country of origin, travel for many reasons-leisure, business, study, to visit family and friends. [1][2][3] Some also travel expressly to have sex. 4 5 Even if sex is not an explicit motivation for travel, sexual encounters may be facilitated through opportunities to meet new people, the loosening of social taboos controlling sexual expression, a sense of anonymity that being away from home confers [5][6][7][8] and in the context of engaging in risk behaviours such as alcohol and drug use, which may also change when away from home.…”
Section: Introductionmentioning
confidence: 99%
“…This issue of Sexually Transmitted Infections contains three papers2–4 on the sexual health of Central and Eastern European (CEE) migrants in London within the SALLEE project (Sexual Attitudes and Lifestyles of London's Eastern Europeans) 5. These papers show new data on the sexual and HIV risk behaviour of CEE migrants,2 their patterns of genitourinary clinic attendance and frequency of sexually transmitted infection (STI) diagnosis3 and explore the sexual risk of CEE migrant men who have sex with men (MSM) 4…”
mentioning
confidence: 99%